Penerapan Model Pembelajaran Demonstrasi Untuk Meningkatkan Hasil Belajar Bahasa Indonesia Siswa Kelas IV SD Kr. 1 Tomobui - Steven Mandey; Anggi Teresia Mamahit (Jurnal Ilmiah Wahana Pendidikan, 2023)
This research aims to improve Indonesian language learning outcomes through the application of a demonstration learning model for fourth grade students at SD Kr.1 Tumobui. The method used in this research is classroom action research (PTK). By using a spiral model. From Kemmis and Mc Taggarat with four stages: (1) Planning, (2) Action, (3) Observation, (4) Reflection. The subjects of this research were fourth grade students at SD Kr. Tumobui. The data collection technique used in this research is the observation technique (observation and test). Meanwhile, the data obtained will be analyzed by calculating the percentage and average of student learning outcomes. The research results showed that the achievement of learning outcomes in cycle I was 66.6%, in cycle II it had increased to 87.5%. Thus, the application of the demonstration learning model can improve speaking learning outcomes for fourth grade students at SD Kr. 1 Tumobui